Transformasi Data Gravitasi Dart Topografi Ke Bidang Datar Dengan Bantuan Perhitungan Sudut Ruang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The application of solid angle computation has been formulated and tested on transfering gravity data from topographic surface to a regular plane surface. The gravity field is formulated as a linear combination of surface density and solid angle of observation point toward the equivalent source, which is a horizontal layer with finite surface density and a limited size. The equivalent sources are continuously scattered underneath the topography. Two kind of equivalent sources are considered. Firstly, equivalent source is a horisontal layer covering the area beneath the topography of observation. Secondly, the equivalent source is not fully a horisontal layer but follows the relief of topography. The topographic relief is formed by horisontal layers which follow the relief of topography. The surface density was determined by an inversion prok..ess of matrix equation of the gravity data and solid angle calculations. Since the size of solid angle matrix was not square so that SVD (Singular Value Decomposition) method is used in inversion process. The transformed gravity field was determined by forward computation using known density surface. The result of theoretical test showed that this method is quite accurate enough to be applied on transformation of gravity field data. The effect of unsimetrical topography was not influetial to accuracy of the method. The depth of equivalent sources depend on the size of equivalent sources. Shape and distribution of mass anomaly were not influential to the accuracy of such method. Comparison between the result of this method with the equivalent source technique by Dampney showed that the relative error of this method was relatively smaller, than Dampney method, although the required time was longer. This is the main reason to choose this method as an alternative one for transformation prucebs of the gravity data to a regular plane surface.